Sequence Analysis of How Disability Influenced Life Trajectories in a Past Population from the Nineteenth-Century Sundsvall Region, Sweden - Lotta Vikström; Helena Haage; Erling Häggström Lundevaller (Historical Life Course Studies)
Historically, little is known about whether and to what extent disabled people found work and formed families. To fill this gap, this study analyses the life course trajectories of both disabled and non-disabled individuals, between the ages of 15 and 33, from the Sundsvall region in Sweden during the nineteenth century. Having access to micro-data that report disabilities in a population of 8,874 individuals from the parish registers digitised by the Demographic Data Base, Umeå University, we employ sequence analysis on a series of events that are expected to occur in life of young adults: getting a job, marrying and becoming a parent, while also taking into account out-migration and death. Through this method we obtain a holistic picture of the life course of disabled people. Main findings show that their trajectories did not include work or family to the same extent as those of non-disabled people. Secondary findings concerning migration and mortality indicate that the disabled rarely out-migrated from the region, and they suffered from premature deaths. To our knowledge this is the first study to employ sequence analysis on a substantially large number of cases to provide demographic evidence of how disability shaped human trajectories in the past during an extended period of life. Accordingly, we detail our motivation for this method, describe our analytical approach, and discuss the advantages and disadvantages associated with sequence analysis for our case study.